MARKET AND PERFORMANCE IMPLICATIONS OF FAST FIT SERVICE CONCEPTS IN AUTOMOTIVE MAINTENANCE SYSTEMS - Velimirovic, Milan; Velimirovic, Dragana; Popovic, Vladimir (Journal of Applied Engineering Science, 2022)
Implementation process of fast fit maintenance service concept in two authorized service networks is shown as well as the results of its empirical implementation, by using descriptive, comparative and statistical analysis method. Implementation of new maintenance service approach shows that its application leads to an improve of the after-sales work performances, relevantly affects the result of the whole business. In particular, in relation to the period when this service concept was not implemented new approach resulted in an increase in the number of total service visits.This research is limited to the automotive maintenance service industry especially as place for an improvement in authorized workshops. But some further studies could refine those measures and process of implementation for the applicability in some other service context.